PAPP-A2 deficiency does not exacerbate the phenotype of a mouse model of intrauterine growth restriction - Julian K. Christians; Kendra I. Lennie; Maria F. Huicochea Munoz; Nimrat Binning (BMC, 2018)
Abstract Background Pregnancy-associated plasma protein-A2 (PAPP-A2) is consistently upregulated in the placentae of pregnancies complicated by preeclampsia and fetal growth restriction. The causes and significance of this upregulation remain unknown, but it has been hypothesized that it is a compensatory response to improve placental growth and development. We predicted that, if the upregulation of PAPP-A2 in pregnancy complications reflects a compensatory response, then deletion of Pappa2 in mice would exacerbate the effects of a gene deletion previously reported to impair placental development: deficiency of matrix metalloproteinase-9 (MMP9). Methods We crossed mice carrying deletions in Pappa2 and Mmp9 to produce pregnancies deficient in one, both, or neither of these genes. We measured pregnancy rates, number of conceptuses, fetal and placental growth, and the histological structure of the placenta. Results We found no evidence of reduced fertility, increased pregnancy loss, or increased fetal demise in Mmp9 −/− females. In pregnancies segregating for Mmp9, Mmp9 −/− fetuses were lighter than their siblings with a functional Mmp9 allele. However, deletion of Pappa2 did not exacerbate or reveal any effects of Mmp9 deficiency. We observed some effects of Pappa2 deletion on placental structure that were independent of Mmp9 deficiency, but no effects on fetal growth. At G16, male fetuses were heavier than female fetuses and had heavier placentae with larger junctional zones and smaller labyrinths. Conclusions Effects of Mmp9 deficiency were not exacerbated by the deletion of Pappa2. Our results do not provide evidence that upregulation of placental PAPP-A2 represents a mechanism to compensate for impaired fetal growth.